Reinterpretasi Hukum Larangan Keluar Rumah Bagi Istri Dalam Masa Idah Raj’i: Telaah Hermeneutika Double Movement Fazlur Rahman - Ahmad Husennafarin (Indonesian Journal of Islamic Law, 2019)
The prohibition against a wife leaving the marital home during the period of ‘iddah raj‘ī, as stated in Qur’ān Surah al-Ṭalāq [65]:1, continues to raise interpretative problems. This article aims to examine the meaning of the obligation for a divorced wife to remain in the house where she was divorced during the ‘iddah raj‘ī period as contained in Qur’ān Surah al-Ṭalāq [65]:1. This study employs Fazlur Rahman’s double movement hermeneutical method, reinforced by the principles of uṣūl al-fiqh. The analysis shows that, from the perspective of Fazlur Rahman’s double movement hermeneutics, the Qur’anic message in Surah al-Ṭalāq [65]:1 is primarily addressed to the husband, emphasizing his responsibility to provide protection for women during the ‘iddah period and to ensure the provision of mut‘ah maintenance for the wife he has divorced. From the standpoint of uṣūl al-fiqh, this reinterpretation of the legal meaning of Surah al-Ṭalāq [65]:1 is consistent with the principles of public welfare (maṣlaḥah) for both parties.